Indians, people, people of African descent in sectors and independence of the government of Popayán (2010)
This article aims to reflect on the participation of popular sectors of the government of Popayan in the process of independence. The participation of popular sectors was sensitized by historiographical tradition dominated by the Creole elites, this vision failed the participation of popular sectors in social movements. It is noteworthy that the participation of these actors, in social movements, contributed to these assum a political role and they see the protest as a mechanism to reject the domination of elites and colonial stuck. So during the campaign led by Simon Bolivar on the release of the government of Popayan, two trends were seen, the inhabitants of Valle del Cauca who defended the independent government project, while residents from Pasto continued to support the royalist army.